Using structural equation modeling to assess the impact of factors on sexual risk and delinquent behavior in Dutch female offenders. (December 2016) - van Horn, J.E.; Reinders, M.; Eisenberg, M.J.; de Lima-Heijns, A.; Posthumus, J.
Abstract: Research shows that juvenile female offenders have a higher prevalence rate of sexual risk behaviors than girls from the general population and that similar factors underlie both SRBs and delinquent behavior. Contributing to findings derived from young female delinquent samples, this study examines the impact of risk factors on delinquent behaviors and sexual risk behaviors in 146 delinquent girls (12 to 18 years) in outpatient forensic treatment. While controlling for ethnicity, results from structural equation modeling through bootstrapping showed that sexual risk behaviors (explained variance 26%) were predicted by the number of negative life events, peer rejection, and substance use, whereas the number of previous convictions and treatment dropout were predictive of delinquent behavior (explained variance 14.1%). Affiliation with deviant peers, parental monitoring, and conduct problems did not contribute to the explained variance in both outcome measures. These findings will be elaborated on in the discussion. Highlights: Empirically supported risk factors for sexual risk and delinquent behavior were studied in the same group of Dutch adolescent girls Negative life events, peer rejection, and substance use explain over 25% of the variation in sexual risk behavior Sexual risk behaviors were particularly present in ethnic minority girls